Grinding and surface quality parameters at automotive parts machining - Novak, Martin; Lattner, Michal; Ruzicka, Ludek; Holesovsky, Frantisek (Manufacturing Technology Journal, 2010)
This paper deals with grinding of the automotive parts and surface quality after grinding. This paper describes results from the experiment with grinding of materials EN ISO 100Cr6 and EN ISO C55E used in automotive industry like materials of the machine parts. This experiment shows possibilities with grinding of this materials and the influence of the ground process parameters during grinding e.g. normal and tangential force, cutting fluids and feed. Together with this experiment is evaluated also the surface quality of machined parts. The evaluated parameters of surface quality were choice roughness and geometrical accuracy - roundness.
Keywords: Cutting forces; feed; grinding surface quality